PARANOID TYPES OF SCHIZOPHRENIA - Tetra Arya Saputra (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Schizophrenia is an terminology of major psychiatric disorders that characterized by changes in perception, thought, affect, and behaviour. The disorder was on 1% of the adult people and generally at the onset of adolescence or age of consent. Paranoid type schizophrenia is the most stable type and often occurred. Mrs. K, 43 years old, present with chief complain of unreasonable anger since one week ago. The patient locked herself in her room and avoided the people. The patient has not drank the medicines since a month ago. The patient has mental disorders history since 1995, and went to outpatients clinic routinely but did not consume the medicines routinely. The medicines were risperidone, stelazine, and trihexylpenidyl, by consuming those patients felt improvement. General and neurologist examination was normal. Blood pressure was 130/80 mmHg, pulse was 82 /minute, respiratory rate was 20x/minute, and temperature was 36,70 C. The psychiatric status self care was good, compos mentis, calm, the talking was spontaneous, cooperative, mood eutimia, the affect was extensive, appropriate, and cognitif was good. There were auditory and visual halusination, no illusion, no depersonalisation or derealialisation. There were delusion of control, delusions of greatness, delusions of pursue, delusions of mystical magic. The judgement capability was interrupted and insight grade 1. The management of risperidone was 2x2 mg/day and also given supportive psychotherapy. The paranoid type schezophrenia is mental disorder that often occured at the end of adolescence or age of consent. [J Agromed Unila 2014; 1(1):42-8] Keywords: diagnose, paranoid, risperidone, schizophrenia